Efficient Synthesis of 2,3′-Spirobi (Indolin)-2′-Ones and Preliminary Evaluation of Their Damage to Mitochondria in HeLa Cells - Li, Huajie; Yu, Zhenjie; Sun, Haoyi; Liu, Bo; Wang, Xin; Shao, Zhe; Wang, Meiling; Xie, Weilin; Yao, Xingang; Yao, Qingqiang; Zhi, Ying (Frontiers in Pharmacology, 2022)
A novel formal [4+1] annulation between N-(o-chloromethyl)aryl amides and 3-chlorooxindoles through in situ generated aza-ortho-QM with 3-chlorooxindoles is reported for the synthesis of a series of 2,3'-spirobi[indolin]-2'-ones in high yields. Under structured illumination microscopy, compound 3a is found to change the mitochondrial morphology and induce mitophagy pathway, which would then trigger apoptosis in cancer cells.